FREQUENCY OF EXTRADURAL HAEMATOMA IN PATIENTS WITH LINEAR SKULL FRACTURE - Aurangzeb, Ahsan; Afridi, Ehtisham Ahmed Khan; Khan, Shahbaz Ali; Muhammad, Gul; Ihsan, Adil; Hussain, Iqbal; Zadran, Khalid Khan; Bhatti, Sajid Nazir (Journal of Ayub Medical College Abbottabad, 2015)
Background: Apparently normal looking patients after traumatic brain injury can have serious neurological deterioration, and one of the common causes of such deterioration is extradural haematomas. This study was conducted to determine the frequency of extradural hematoma and common types of trauma leading to it among patients presenting with skull fracture due to head injury. Methods: This cross-sectional study was conducted in the department of Neurosurgery Ayub Medical College, Abbottabad from June 2011 to June 2012. All patients who were suspected to have Skull fracture on X-ray skull, during the study period, were included in study after informed consent and later on CT-Scan brain was done to see for extradural hematoma. Findings were recorded on a predesigned pro forma including demographic data, radiological findings and the type of head trauma. Results: Out of 114 patients 85 (74.5%) were males and 29 (225.4%) were females. Age ranged from 2 to 70 years (18.23±16.5 years). Among these patients the most important cause of head injury was fall from height in 65(57%), followed by road traffic accidents in 39 (34.2%), and assault in 10 (8.8%) patients. The most common site of fracture was parietal in 49 (43%) of patients, followed by frontal bone in 28 (24.6%) of patients, occipital bone in 24 (21.1%) of patients, and temporal bone in 23 (20.2%) of patients. Frequency of extradural hematoma among linear skull fracture was in 34 (29.8%) patients. Extradural hematoma was most common with parietotemporal linear skull fractures (73.5%). Conclusion: Extradural haematoma occurs commonly with linear skull fractures, so patients with linear skull fracture should be properly evaluated with CT brain. Keywords: Head injury, extradural haematoma, linear skull fracture.